Hilar Cholangiocarcinoma - Lau, W.Y.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This is a multi-author book on hilar cholangiocarcinoma, written by an international team of world-renowned experts covering topics in their respective areas of expertise. There are altogether 71 authors from 14 countries/regions, mainly Argentina, Australia, China, Germany, Italy, Japan, Korea, Malaysia, Thailand, the Netherlands, the United Kingdom and the United States of America.   This book aims to provide an up-to-date, fully referenced text that is as succinct as possible, but as comprehensive as necessary, addressing all topics in hilar cholangiocarcinoma. It provides the latest findings in the rapidly advancing field of hilar cholangiocarcinoma. Controversial aspects are discussed by highly regarded authorities who look at the problem from different perspectives. A helpful list of references is included at the end of each chapter. The extensive use of diagrams, figures and tables makes the text easy to read.   This book is primarily intended for clinicians and researchers who are interested in hilar cholangiocarcinoma, including liver surgeons, hepatologists, interventional and diagnostic radiologists, and basic researchers. General physicians, general surgeons, trainees, epidemiologists, hospital administrators, pathologists and instrument manufacturers will also find this book to be a valuable reference work.   Editor Lau is currently a Professor of Surgery at the Chinese University of Hong Kong, and an Academician of Chinese Academy of Sciences, China.
Anatomy of the Hepatic Hilum -- Epidemiology -- Pathology -- Staging Systems -- Preoperative Imaging -- Role of 3D Reconstructive Imaging -- Assessment of Liver Function -- Diagnosis -- Differential Diagnosis -- Molecular Markers of Cholangiocarcinoma -- Laparoscopy and Laparoscopic Ultrasound -- Preoperative Optimization of the Liver for Resection -- Preoperative Biliary Drainage -- Portal Vein Embolization -- Anesthesia for Patients with Hilar Chlolangiocarcinoma -- Selection of Patients for Liver Resection and Liver Transplantation -- History of Surgery in Hilar Cholangiocarcinoma -- Radical Resection and Its Limits -- Central Lobectomy -- Extended Resections -- Combined Liver Resection and Portal Vein Resection -- The Hepatic Artery Reconstruction First Approach in Hilar Cholangiocarcinoma Type Ⅲb -- Local Resection without Hepatectomy -- Ex Situ Ex Vivo Resection and Autotransplantation -- Liver Transplantation -- Neoadjuvant/adjuvant Therapy for Liver Resection and Transplantation -- Palliative Surgical Treatment -- Palliation by Endoscopic Approach -- Percutaneous Palliation of Cholangiocarcinoma -- Photodynamic Therapy -- Radiation and Chemotherapy.
Keywords: Surgical oncology; Hepatology; Surgery; Surgical Oncology; Hepatology; Surgery